BUSINESS STRATEGY OF STARTUP COMPANY TO INCREASING REVENUE ON EXPRESS COURIER INDUSTRY (CASE STUDY NINJA VAN/NINJA XPRESS INDONESIA) - Andreyanto, Ivan
Huge growth of digital environment that has occurred on other parts of the world has also happening in Indonesia. which estimated in 2020 up to 50 million internet with penetration number up to 55%. Seeing this potential and significant number also drives the digital trading industry which in 2019 has contributed up to 2.9% of Indonesia's total GDP. At present, there are an additional 6 marketplace that have the largest market share in the digital trading industry such as Tokopedia, Shoopee, Bukalapak, Bli-bli, Lazada and JD.ID and the other 3 is came from Indonesa (Tokopedia, Bukalapak and Bli-bli). A comfortable way of transaction and safe purchasing experience with a complete product selection has made those six companies became the choice e-commerce companies in Indonesia with more than 1 million package transactions and is predicted to increase 1.6 million packages in 2022.